Double blind, placebo controlled study of nedocromil sodium in asthma. - Armenio, L (1993)
After a two week baseline, 209 asthmatic children (mean age 10 years, range 6-17) were randomly allocated to receive 4 mg nedocromil sodium (n = 110) or placebo (n = 99) four times daily for 12 weeks in addition to their current treatment. The children completed daily diary cards and visited the clinic at four week intervals. Statistically significant differences in favour of nedocromil sodium were seen for clinician assessment of asthma severity and diary card symptom scores, pulmonary function and inhaled beta 2 bronchodilator use. Total symptom score decreased by 50% from baseline in the nedocromil sodium group and by 9% in the placebo group during the final four weeks. Nedocromil sodium was considered very or moderately effective by 78% of children/parents (placebo 59%) and 73% of clinicians (placebo 50%). Nausea, headache and sleepiness, and dyspnoea led to withdrawal of one child from nedocromil sodium and placebo treatments, respectively. Reports of sore throat and headache were marginally greater with the nedocromil sodium treatment. It is concluded that nedocromil sodium was both effective and safe in the treatment of asthma in children.